Darwin and his children : his other legacy - Berra, Tim M., 1943- (Oxford University Press, 2013)
While much has been written about the life and works of Charles Darwin, the lives of his ten children remain largely unexamined. Most ""Darwin books"" consider his children as footnotes to the life of their famous father and close with the death of Charles Darwin. This is the only book that deals substantially with the lives of his children from their birth to their death, each in his or her own chapter. Tim Berra's Darwin and His Children: His Other Legacy explores Darwin's marriage to his first cousin, Emma Wedgwood, a devout Unitarian, who worried that her husband's lack of faith would keep.